AVAILABLE MICRONUTRIENTS IN SANDY SOILS OF RAJASTHAN - Baser, B L; Lodha, P S (Annals of Arid Zone, 2016)
Soil samples representing sandy region of Rajasthan were analysed for the available content of micronutrient elements. Exchangeable manganese, reducible manganese, available copper, boron and iron were found to range between 0.40 ppm, to 5.20 ppm, 9.20 ppm to 62.65 ppm, 0.05 ppm to 2.38 ppm, 0.03 ppm to 1.54 ppm and 0.64 ppm to 8.50 ppm respectively. These soils were found to be deficient in manganese while considered to have adequate quantity of available copper and boron for good crop growth. Effect of pH, calcium carbonate and organic matter content of solis on the availability of these nutrients was also calculated statistically and discussed.